Rubble : The Afterlife of Destruction - Gordillo, Gastón R. (Book collections on Project MUSE., 2014)
Based on ethnographic research in the foothills of the Argentine Andes, Gastón R. Gordillo reveals the spatial, historical, and affective ruptures embodied in debris. For the rural poor, the rubble left in the wake of capitalist and imperialist endeavors is not romanticized ruin but the material manifestation of the violence and dislocation that created it.